RETHINKING REGULATION: INCLUSIONS, EXCLUSIONS AND STRUGGLES - Baines, Donna; Clark, Natalie; Riley, Jeane (Canadian Social Work Review / Revue canadienne de service social, 2022)
A recent government report in British Columbia on anti-Indigenous racism in health care calls into question the claim that regulating health care professionals protects the public and ensures a high standard of professional, ethical care. Licensure and regulation have long been debated in social work with strong advocates on each side. The first section of this article revisits the historical and contemporary pro-registration and pro-inclusion arguments. Drawing on publicly available documents central to licensure and regulation in BC, the article then draws on two policy analysis frameworks, namely Indigenous Intersectional-Based Policy Analysis and Bacchi’s framework to explore “what is the problem represented to be” and who is positioned as problematic and erased or delegitimized within these processes. The analysis shows that the regulation debate is a series of practices of power that frame which issues will be “raised and which will not be discussed” such as “harm” and “protection”, while simultaneously eclipsing Indigenous and other non-dominant cultural perspectives and concerns. Our analysis further suggests that mandatory registration constructs the problems facing social workers in depoliticized and narrow ways that do not extend social justice, reconciliation, or decolonization, and require a serious rethink at this moment of change and challenge.